(untitled) (The Review of Diabetic Studies, 2025)
This study aims to identify paramedics’ perceptions of the use of virtual hospitals to support pre-hospital emergency medical care, given the increasing importance of this technology in improving the quality of healthcare services and the speed of response to critical cases. The research relied on the descriptive analytical approach by preparing a questionnaire consisting of eight items distributed on a five-point Likert scale, and included a sample of **500 paramedics working in emergency medical services. The results showed that the sample members’ perceptions of virtual hospitals were moderately to highly positive, with the arithmetic means of the items ranging between (3.7 - 4.2), reflecting the participants’ belief in the effectiveness of this technology in improving medical decision-making, increasing diagnostic accuracy, and reducing response time to emergency cases. The results also showed that virtual hospitals contribute to improving the quality of pre-hospital care, enhancing coordination between paramedics and specialist physicians, and supporting paramedics’ professional development through direct communication with experts. Statistical differences tests (T-test and ANOVA) showed no statistically significant differences attributable to gender, while differences related to years of experience appeared in favor of those with more than ten years of experience, indicating that practical experience enhances acceptance of this technology and appreciation of its importance. The study emphasizes the importance of expanding the application of virtual hospital technologies in field settings, while providing training programs for paramedics to enhance their proficiency in using this technology, thus contributing to improving the quality of emergency care and reducing medical errors.